Vaginal misoprostol versus intracervical Foley catheter for cervical ripening in postdate primigravid women: a randomized clinical trial - Nazanin Abdi; Azin Alavi; Forough Pakbaz; Hossein Darabi (BMC, 2021)
Abstract Background Being one of the most common indications of labor induction, postdate pregnancy can lead to serious maternal and fetal complications. In this study we aimed to compare vaginal misoprostol with intracervical Foley catheter (FC) for cervical ripening in postdate primigravid women. Methods This randomized clinical trial included 120 primigravid women aged 18-35 years with singleton,  postdate pregnancies, and Bishop score ≤ 4. Participants were randomized into two equal groups. The first group received 25 µg vaginal misoprostol and the second group had an 18 Fr FC inserted into their cervical canal. Labor induction was performed using oxytocin in both groups if progression of labor or true contractions did not occur within 6 h of the interventions. In case of nonreassuring fetal heart rate, fetal distress, placental abruption, or prolonged labor, C-section was performed. Results The frequency of normal vaginal delivery, Cesarean section, meconium-stained amniotic fluid, and neonatal intensive care unit admission did not differ significantly between groups. Placental abruption and uterine tachysystole occurred more frequently in the misoprostol group (15.0 vs. 1.7%, P = 0.008 and 21.7 vs. 0.0%, P < 0.001, respectively). A significantly higher number of women in the FC group required oxytocin (73.3 vs. 41.7%, P < 0.001). Duration of labor was significantly higher in the FC group (P = 0.001). Conclusions Due to the lower rate of placental abruption and uterine tachysystole observed with FC, it appears to be superior to vaginal misoprostol for cervical ripening in postdate primigravid women; however, its longer labor duration and higher oxytocin requirement should be taken into consideration. Trial registration Iranian Registry of Clinical Trials, IRCT20181218042033N4 . Registered 19/04/2020. Retrospectively registered, https://www.irct.ir/trial/47037